INTERNALISASI NILAI-NILAI AHLUSSUNNAH WAL JAMA‘AH SEBAGAI FONDASI PEACE EDUCATION DI ERA GLOBAL - Saifuddin, Abidatul Quddus (PRODI PAI FIK UNIRA MALANG, 2025)
This study examines the importance of internalizing the values of Ahlussunnah wal Jama‘ah (Aswaja) as the foundation of Peace Education in the global era. Aswaja, as the religious manhaj (methodology) of the majority of Indonesian Muslims, emphasizes the principles of moderation (tawassuth), balance (tawazun), tolerance (tasamuh), and justice (i‘tidal). These principles are closely related to Peace Education, which aims to build a culture of peace, promote non-violent conflict resolution, and encourage respect for diversity. The research method used is a case study approach. Data collection was conducted using three techniques: observation, interviews, and documentation. In addition, a literature review was carried out by analyzing references on Aswaja and Peace Education. The findings of the study show that: 1) The concept of Aswaja values at SMP Islam Kalipare is based on the values of tawassuth, i‘tidal, tawazun, and tasamuh. 2) The process of instilling Aswaja values takes place in three stages: a) Aswaja Knowing–understanding through learning activities inside and outside the classroom, such as religious activities. b) Aswaja Feeling–habituating students to practice Aswaja values in school. c) Aswaja Action–implementing these habituated values both inside and outside the school. 3) The results of internalizing Aswaja values include strengthening Islamic piety in line with a moderate, tolerant, and humanistic Ahlussunnah wal Jama‘ah identity. This is reflected in students’ social attitudes: they are not fanatical toward anyone, are fair to themselves and others, maintain balance in social relations and worship to Allah SWT, and are able to accept and respect differences. Consequently, they can live harmoniously and peacefully in society. The internalization of Aswaja values through Islamic educational institutions can reinforce the moderate character of the younger generation, prevent radicalism, and contribute to global peace.